Impact of health research on advances in knowledge, research capacity-building and evidence-informed policies: a case study on maternal mortality and morbidity in Brazil - Angulo-Tuesta, Antonia; Santos, Leonor Maria Pacheco; Natalizi, Daniel Alves (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: National health research systems aim to generate high-quality knowledge so as to maintain and promote the population’s health. This study aimed to analyze the impact of maternal mortality/morbidity research funded by the Brazilian Ministry of Health and institutional partners, on the dimensions: advancing in knowledge, research capacity-building and informing decision-making, within the framework of the Canadian Academy of Health Sciences. DESIGN AND SETTING: Descriptive study based on secondary data, conducted at a public university. METHODS: The advancing in knowledge dimension was estimated from the principal investigators’ publication counts and h-index. Data on research capacity-building were obtained from the Ministry of Health’s information system. The informing decision-making dimension was analyzed from citations in Stork Network (Rede Cegonha) documents. RESULTS: Between 2002 and 2010, R$ 21.6 million were invested in 128 maternal mortality/morbidity projects. Over this period, the principal investigators published 174 articles, resulting in an h-index of 35, thus showing progress in the advancing in knowledge dimension. Within the research capacity-building dimension, training of 71 students (undergraduate/postgraduate) was observed. Progress in the informing decision-making dimension was modest: 73.5% of the 117 citations in the Stork Network documents were institutional documents and norms. One of the projects funded, the 2006/7 National Demography and Health Survey, was cited in program documents. CONCLUSION: Impacts were shown in the advancing in knowledge and research capacity-building dimensions. The health research system needs to incorporate research for evidence-informed policies.